2020
DOI: 10.1101/2020.07.27.20162842
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of D-dimer and fibrinogen magnitude with hypercoagulability by thromboelastography in severe COVID-19

Abstract: Introduction: D-dimer concentration has been used to identify candidates for intensified anticoagulant treatment for both venous thromboembolism prevention and mitigation of the microthrombotic complications associated with COVID-19. Thromboelastography (TEG) maximum amplitude (MA) has been validated as an indicator of hypercoagulability and MA ≥ 68 mm has been utilized as a marker of hypercoagulability in other conditions. We evaluated the relationship between coagulation, inflammatory, and TEG parameters in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A LY30 value of 0% combined with elevated D-dimer levels was also found to predict the need for dialysis treatment for acute renal failure in 80% of patients [25]. Chandel et al (2020) found that D-dimer results were less consistent for assessing hypercoagulability in patients treated with extracorporeal membrane oxygenation (ECMO), which plays a key role in COVID-19 management and treatment, reporting a significant negative correlation between thromboelastography identified hypercoagulability in patients with and without macrothrombosis [16]. This is in line with results from research that suggest that ECMO support, with TEG measurements used for ensuring ECMO maintenance, can be an integral part of critical care for patients with COVID-19 [27].…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…A LY30 value of 0% combined with elevated D-dimer levels was also found to predict the need for dialysis treatment for acute renal failure in 80% of patients [25]. Chandel et al (2020) found that D-dimer results were less consistent for assessing hypercoagulability in patients treated with extracorporeal membrane oxygenation (ECMO), which plays a key role in COVID-19 management and treatment, reporting a significant negative correlation between thromboelastography identified hypercoagulability in patients with and without macrothrombosis [16]. This is in line with results from research that suggest that ECMO support, with TEG measurements used for ensuring ECMO maintenance, can be an integral part of critical care for patients with COVID-19 [27].…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Evidence suggests that even increased markers of coagulation and fibrinolytic activation can be found in septic patients without correlation with impaired fibrinolytic activity measured by VET or other global fibrinolysis tests [63]. Equally, patients under ECMO showed onlya poor correlation of D-dimer values and hypercoagulability measured by VET [72]. In the study by Bachler et al D-dimer levels were useful in predicting impaired fibrinolysis in contrast to VET [40].…”
Section: Predictive Ability Of Vet Compared To Conventional Laborator...mentioning
confidence: 98%
“…Recently, various papers have shown the significance of TEG ® and the levels of coagulopathy in COVID-19 (an important measurement value of the TEG ® ) in managing COVID-19 patients is also getting more traction (Chandel, et al 2021, Görlinger and Levy 2021, Hranjec, et al 2020) (Smolarz, et al 2021). Hranjec and co-workers in 2020 also noted that TEG ® with platelet mapping, better characterizes the spectrum of COVID-19 coagulation-related abnormalities and may guide more tailored, patient-specific therapies these patients (Hranjec, et al 2020).…”
Section: Significant Evidence For Hypercoagulation During the Early Stages Of Covid-19 Diseasementioning
confidence: 99%